Abrasion-resistant water-based anticorrosive paint for hydraulic concrete, and preparation method and coating of erosion-resistant water-based anticorrosive paint

By using a combination of modified steel slag powder and alkaline regulators, the impact-resistant wear performance and bonding strength of hydraulic concrete anti-corrosion coatings are improved, and the fragility of existing coatings under high-speed water flow erosion is solved. It is suitable for marine and other Severe environment.

CN119286346AActive Publication Date: 2025-01-10WUHAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411361762.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-10
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing hydraulic concrete anti-corrosion coatings have shortcomings in impact wear performance and bonding strength, and cannot effectively resist high-speed water flow erosion, resulting in easy damage and falling off of the coating.

Method used

The main components are used to improve the strength and toughness of the steel slag powder through ball milling and carbonization modification, and the alkaline regulators are improved by alkaline regulators. Combined, it forms a water-based anti-corrosion coating with high impact wear performance.

Benefits of technology

It significantly improves the impact wear and bonding strength of the coating, is suitable for harsh water flow environments, and is simple in process and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-abrasion hydraulic concrete water-based anticorrosive paint, a preparation method thereof and a coating. The abrasion-resistant hydraulic concrete water-based anticorrosive paint is prepared from the following raw materials in parts by weight: 10 to 40 parts of water-based epoxy resin emulsion, 10 to 40 parts of modified steel slag powder, 10 to 50 parts of alkaline regulating agent and 10 to 40 parts of water-based epoxy curing agent. On the basis of high wear resistance of the steel slag, the modified steel slag powder with higher strength and higher toughness is obtained through modification, and the modified steel slag powder and the alkaline regulating agent are synergistically used as a modified filler of an epoxy component, so that the defect of poor combination of an epoxy coating and an inorganic filler can be remarkably improved, and the service life of the coating is prolonged. And the abrasion resistance is improved. The adopted steel slag raw material is solid waste and is low in cost and wide in source, the steel slag modification process is short in time, and the preparation process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reinforced concrete anti-corrosion coatings, and in particular to an abrasion-resistant water-based anti-corrosion coating for hydraulic concrete, a preparation method thereof and a coating. Background Art

[0002] During the use of hydraulic concrete structures, due to high-speed water scouring and cavitation, concrete cracking, peeling and other defects are prone to occur, which destroys the stability of the overall structure and accelerates the corrosion and damage of internal steel bars. There are huge safety hazards and high maintenance costs. Coating protection technology is the most widely used method to improve the service life of hydraulic concrete structures. Its construction method is simple and low-cost. Traditional coating components are mainly organic coatings and inorganic coatings. Among them, organic coatings have dense film formation, good protective effect, and strong adhesion to the concrete matrix, but they have poor weather resistance and are prone to bulging when the internal water of the concrete evaporates outwards; inorganic coatings have good weather resistance, but at the same time they have problems such as high brittleness and easy cracking. In addition, existing protective coatings are rarely designed from the perspective of abrasion resistance, and cannot resist high-speed water scouring, making the coating easily damaged and falling off.

[0003] Steel slag is a bulk solid waste product produced in the processes of steel smelting, converters, electric furnaces and continuous casting. The main mineral phases of steel slag include tricalcium silicate, dicalcium silicate, calcium magnesium olivine, calcium magnesium rhodonite, calcium aluminoferrite, etc., which usually have high hardness, high temperature resistance, corrosion resistance and high carbonization activity. Chinese invention patent CN201710464395.4 discloses a wear-resistant coating prepared from steel slag, a wear-resistant coating coating block and a preparation method. The wear-resistant coating of the invention is made of raw steel slag, epoxy resin and curing agent, wherein the particle size of the steel slag is in the range of 1-1.5 mm and 3-3.5 mm. The invention mainly improves the wear resistance by using raw steel slag as filler and particle grading stacking. There is a problem of desorption between the steel slag and the two phases due to the shrinkage of epoxy resin curing, and the high hardness and impact resistance of the steel slag cannot be exerted.

[0004] Therefore, the development of new hydraulic concrete anti-corrosion coatings with high weather resistance, high bonding strength and high abrasion resistance has important practical and economic value. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, propose a water-based anti-corrosion coating for abrasion-resistant hydraulic concrete, its preparation method and coating, and solve the technical problem in the prior art that the bonding strength and abrasion resistance of wear-resistant coatings based on steel slag need to be improved.

[0006] In a first aspect, the present invention provides a water-based anti-corrosion coating for impact-resistant hydraulic concrete. The raw materials thereof include, by weight: 10 to 40 parts of water-based epoxy resin emulsion, 10 to 40 parts of modified steel slag powder, 10 to 50 parts of alkaline regulator, and 10 to 40 parts of water-based epoxy curing agent.

[0007] In a second aspect, the present invention provides a method for preparing a water-based anticorrosive coating for abrasion-resistant hydraulic concrete, comprising the following steps: The water-based epoxy resin emulsion, modified steel slag powder, water-based epoxy curing agent and alkaline regulating agent are uniformly mixed to obtain a water-based anti-corrosion coating for abrasion-resistant hydraulic concrete.

[0008] In a third aspect, the present invention provides an abrasion-resistant hydraulic concrete water-based anti-corrosion coating, which is obtained by applying the abrasion-resistant hydraulic concrete water-based anti-corrosion coating provided by the first aspect of the present invention to the surface of a substrate and drying it.

[0009] Compared with the prior art, the beneficial effects of this application include: The water-based anti-corrosion coating for abrasion-resistant hydraulic concrete of the present invention obtains modified steel slag powder with higher strength and higher toughness based on the high abrasion resistance of steel slag, and cooperates with an alkaline regulator as a modified filler of an epoxy component, which can significantly improve the disadvantage of poor combination between epoxy coating and inorganic filler and improve its abrasion resistance. The steel slag raw material used in the present invention is solid waste, which has low cost and wide sources, and the steel slag modification process time is short and the preparation process is simple. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0011] The wear-resistant coating of the prior art is a composite of a highly wear-resistant steel slag component in an organic component epoxy resin, and mainly uses untreated steel slag particles to provide anti-wear performance. There is only physical bonding between the steel slag and the epoxy resin, and the organic-inorganic combination is not tight. The internal organic phase will produce weak points under impact, so that the coating does not have sufficient anti-wear performance and cannot give full play to the high hardness and anti-wear performance characteristics of the steel slag. At the same time, due to the volume shrinkage of the epoxy resin organic component during the curing and cross-linking process, it is easy to cause gaps or shear stresses between the coating and the substrate, thereby weakening the adhesion and protective performance of the coating. In addition, water-based anti-corrosion coatings are an important development direction due to their easy construction and low VOC emissions.

[0012] Based on this, the present invention is proposed.

[0013] In a first aspect, the present invention provides a water-based anti-corrosion coating for impact-resistant hydraulic concrete. The raw materials thereof include, by weight: 10 to 40 parts of water-based epoxy resin emulsion, 10 to 40 parts of modified steel slag powder, 10 to 50 parts of alkaline regulator, and 10 to 40 parts of water-based epoxy curing agent.

[0014] The water-based anti-corrosion coating for abrasion-resistant hydraulic concrete of the present invention obtains modified steel slag powder with higher strength and higher toughness based on the high abrasion resistance of steel slag, and cooperates with an alkaline regulator as a modified filler of an epoxy component, which can significantly improve the disadvantage of poor combination between epoxy coating and inorganic filler and improve its abrasion resistance. The steel slag raw material used in the present invention is solid waste, which has low cost and wide sources, and the steel slag modification process time is short and the preparation process is simple.

[0015] In this embodiment, the preparation steps of modified steel slag powder include: The steel slag, the crystal form control agent and water are mixed uniformly, and then dried, ball-milled and sieved to obtain the undersize; The sieved material is subjected to carbonization modification treatment to obtain modified steel slag powder.

[0016] The present invention can improve the specific surface area of ​​steel slag and increase the number of surface active groups through ball milling treatment; and can form an aragonite high-toughness layer on the surface of steel slag powder through carbonization modification treatment, so as to improve the strength and toughness of steel slag powder. In addition, after ball milling and carbonization modification of steel slag particles in the present invention, the intercalation between steel slag particles and epoxy resin components can be enhanced, effectively resisting the volume shrinkage during the curing process of epoxy resin, thereby improving the bonding strength between the coating and the substrate.

[0017] Preferably, the crystal form control agent is at least one of magnesium chloride, magnesium sulfate, potassium chloride and sodium phosphate. The present invention can inhibit the formation of calcite during the carbonization modification process by adding the crystal form control agent, and induce the formation of an aragonite high-toughness layer on the surface of the steel slag powder.

[0018] Preferably, the amount of the crystal control agent added is 0.5-3% of the mass of the slag, including but not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc.

[0019] Preferably, the amount of water added is 1 to 10 times the mass of the slag, including but not limited to 1 times, 2 times, 4 times, 6 times, 8 times, 10 times, etc.

[0020] Preferably, mixing is performed using a mixer, and the mixing time is 1 to 2 hours.

[0021] Preferably, the drying temperature is 40 to 80° C., and the drying time is 12 to 36 hours.

[0022] Preferably, ball milling is performed using a ball mill, and the ball milling time is 0.5 to 1 h.

[0023] Preferably, the mesh size of the sieve is 100 to 300 meshes.

[0024] Preferably, during the carbonization modification process, the humidity is 90% to 95%, the temperature is 70 to 90°C, the pressure is 0.2 to 0.3 MPa, the carbonization time is 1 to 3 hours, and the CO 2 The volume concentration of the gas is 40-100%. The carbonization modification treatment is carried out in a carbonization reaction container. The present invention is more conducive to the formation of the aragonite high-toughness layer by controlling the carbonization temperature at 70-90°C.

[0025] The present invention is to 2 The source of the gas is not limited, and those skilled in the art can select it according to the actual situation. 2 The gas may be CO-rich 2 Industrial furnace exhaust or commercial high-concentration CO 2 Gas, etc.

[0026] More preferably, during the carbonization modification process, the screen undersize can be spread out to increase the contact between the screen undersize and CO. 2 The contact area of ​​the gas is increased to make the carbonization more complete.

[0027] In this embodiment, the waterborne epoxy resin emulsion is a cationic waterborne epoxy resin emulsion. The present invention does not limit the type of cationic waterborne epoxy resin emulsion, and those skilled in the art can select it according to actual conditions, for example, it can be an amine-modified cationic waterborne epoxy resin emulsion, further, it can be a diethanolamine-modified cationic waterborne epoxy resin emulsion, a diallylamine-modified cationic waterborne epoxy resin emulsion, etc.

[0028] In some specific embodiments of the present invention, the preparation method of the amine-modified cationic waterborne epoxy resin emulsion includes: dissolving E-44 epoxy resin in butanone, heating to 70-80°C in a nitrogen environment, stirring until the resin is completely dissolved, adding 9-11 parts of an amine compound, continuing the reaction for 1-2 hours and then cooling, adding acrylic acid under stirring until the pH is 5-6, and finally adding deionized water to dilute to the target solid content to obtain a cationic waterborne epoxy resin emulsion.

[0029] In this embodiment, the solid content of the water-based epoxy resin emulsion is 30-60%, including but not limited to 30%, 40%, 50%, 60%, etc.

[0030] In this embodiment, the curing agent is at least one of 8310 self-emulsifying epoxy curing agent, GCA02 water-based epoxy curing agent, and 810 curing agent.

[0031] In the present embodiment, the alkaline control agent is a dicalcium silicate mineral, further at least one of γ-type dicalcium silicate and β-type dicalcium silicate, preferably γ-type dicalcium silicate. Dicalcium silicate minerals usually do not have hydration activity, but will rapidly release calcium hydroxide after combining with water, and maintain a high alkaline environment with a pH of about 12 for a long time. After compounding with a water-based epoxy resin, the demulsification of the water-based epoxy resin can be further promoted by high alkalinity. Compared with the demulsification process of cement-polymer emulsion, the demulsification process is accelerated more gently by using the alkaline control agent of the present invention, and the combination between the demulsification film of organic matter and inorganic materials is closer, so that rapid demulsification and agglomeration of organic particles will not occur.

[0032] In this embodiment, the abrasion-resistant water-based anticorrosive coating for hydraulic concrete comprises, by weight, 20 parts of water-based epoxy resin emulsion, 10 to 40 parts of modified steel slag powder, 10 to 30 parts of alkaline regulator, and 20 parts of water-based epoxy curing agent.

[0033] In this embodiment, the raw materials of the abrasion-resistant hydraulic concrete water-based anti-corrosion coating also include: a diluent.

[0034] Preferably, the diluent is at least one of anhydrous ethanol, ethylene glycol, propylene glycol, and isopropanol.

[0035] Preferably, the amount of diluent added accounts for 0.05-5% of the total mass of the water-based anti-corrosion coating for abrasion-resistant hydraulic concrete, including but not limited to 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, etc.

[0036] In a second aspect, the present invention provides a method for preparing a water-based anticorrosive coating for abrasion-resistant hydraulic concrete, comprising the following steps: The water-based epoxy resin emulsion, modified steel slag powder, water-based epoxy curing agent and alkaline regulating agent are uniformly mixed to obtain a water-based anti-corrosion coating for abrasion-resistant hydraulic concrete.

[0037] In some specific embodiments of the present invention, the method for preparing the abrasion-resistant hydraulic concrete water-based anticorrosive coating comprises the following steps: The water-based epoxy resin emulsion and the modified steel slag powder are uniformly mixed to obtain component A; The waterborne epoxy curing agent and the alkaline control agent are mixed evenly to obtain component B; The A component and the B component are mixed evenly to obtain the abrasion-resistant hydraulic concrete water-based anticorrosive coating.

[0038] In a third aspect, the present invention provides an abrasion-resistant hydraulic concrete water-based anti-corrosion coating, which is obtained by applying the abrasion-resistant hydraulic concrete water-based anti-corrosion coating provided by the first aspect of the present invention to the surface of a substrate and drying it.

[0039] In this embodiment, the substrate is concrete.

[0040] In this embodiment, the substrate needs to be pretreated before coating.

[0041] In some specific embodiments of the present invention, the step of pre-treating the substrate includes: removing defects and damaged parts on the surface of the concrete, removing surface dust and debris with high-pressure water, and then drying the concrete machine.

[0042] In this embodiment, the coating step includes: using a wool roller to evenly apply the above-mentioned anti-abrasion hydraulic concrete water-based anti-corrosion coating to the concrete surface.

[0043] Preferably, apply 2 to 3 times.

[0044] In this embodiment, the coating thickness is 0.5 to 3 mm, preferably 1 to 1.5 mm.

[0045] In this embodiment, the drying method is natural drying, and the drying time is 12 to 36 hours.

[0046] To avoid redundant description, in the following embodiments and comparative examples of the present invention, the preparation method of the amine-modified cationic waterborne epoxy resin emulsion is as follows: Preparation of diethanolamine modified cationic waterborne epoxy resin emulsion: 10 parts of E-44 epoxy resin (mass solid content 80%) were dissolved in 20 parts of butanone, heated to 80°C in a nitrogen environment, stirred until the resin was completely dissolved, and 11 parts of diethanolamine were added, and the reaction was continued for 1 hour. The above product was cooled to 40°C, acrylic acid was added under stirring until the pH was 5.5, and deionized water was added to dilute to a solid content of 40%, to obtain a diethanolamine modified cationic waterborne epoxy resin emulsion.

[0047] Preparation of diallylamine modified cationic waterborne epoxy resin emulsion: 10 parts of E-44 epoxy resin (mass solid content 80%) were dissolved in 20 parts of butanone, heated to 70°C in a nitrogen environment, stirred until the resin was completely dissolved, and 9 parts of diallylamine were added, and the reaction was continued for 1 hour. The above product was cooled to 40°C, acrylic acid was added under stirring to a pH of 5.5, and deionized water was added to dilute to a solid content of 40%, to obtain a diallylamine modified cationic waterborne epoxy resin emulsion.

[0048] Example 1 The preparation steps of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete of this embodiment are as follows: (1) Weigh 300 parts of raw steel slag, 5 parts of magnesium chloride crystal form control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0049] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0050] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0051] (4) Take 30 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0052] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0053] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0054] (7) Leave the components in the air to dry naturally for 24 hours.

[0055] Example 2 The preparation steps of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete of this embodiment are as follows: (1) Weigh 300 parts of raw steel slag, 2 parts of magnesium chloride crystal form control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0056] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0057] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0058] (4) Take 30 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0059] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0060] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0061] (7) Leave the components in the air to dry naturally for 24 hours.

[0062] Example 3 The preparation steps of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete of this embodiment are as follows: (1) Weigh 300 parts of raw steel slag, 8 parts of magnesium chloride crystal control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0063] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0064] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0065] (4) Take 30 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0066] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0067] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0068] (7) Leave the components in the air to dry naturally for 24 hours.

[0069] Example 4 The preparation steps of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete of this embodiment are as follows: (1) Weigh 300 parts of raw steel slag, 5 parts of magnesium sulfate crystal control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0070] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0071] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of diallylamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0072] (4) Take 30 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0073] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0074] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0075] (7) Leave the components in the air to dry naturally for 24 hours.

[0076] Example 5 The preparation steps of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete of this embodiment are as follows: (1) Weigh 300 parts of raw steel slag, 9 parts of magnesium sulfate crystal form controller, and 3000 parts of water by weight, add them into a mixer and mix for 1 hour. After being fully mixed, put them into an oven at 80°C to dry for 36 hours, and then put them into a ball mill to grind for 1 hour.

[0077] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0078] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0079] (4) Take 10 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0080] (5) Evenly mix the above components A and B, add 2 parts of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0081] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0082] (7) Leave the components in the air to dry naturally for 24 hours.

[0083] Example 6 The preparation steps of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete of this embodiment are as follows: (1) Weigh 300 parts of raw steel slag, 8 parts of potassium chloride crystal control agent, and 600 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 1 hour.

[0084] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0085] (3) Taking 40 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0086] (4) Take 30 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0087] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0088] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0089] (7) Leave the components in the air to dry naturally for 24 hours.

[0090] Example 7 The preparation steps of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete of this embodiment are as follows: (1) Weigh 300 parts of raw steel slag, 5 parts of magnesium chloride crystal form control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0091] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0092] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0093] (4) Take 30 parts of β-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0094] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0095] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0096] (7) Leave the components in the air to dry naturally for 24 hours.

[0097] Comparative Example 1 In step (2) of comparative example 1, the steel slag powder was not modified, and other conditions and steps were the same as those of example 1, as follows: (1) Weigh 300 parts of raw steel slag, 5 parts of magnesium chloride crystal control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0098] (2) Pass the ground powder through a 200-mesh sieve to obtain the steel slag powder that falls under the sieve and set it aside for later use.

[0099] (3) Taking 10 parts by weight of the above-mentioned undersize steel slag powder as a coating modification component, add it into 20 parts of diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0100] (4) Take 30 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0101] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0102] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0103] (7) Leave the components in the air to dry naturally for 24 hours.

[0104] Comparative Example 2 In step (1) of comparative example 2, no magnesium chloride crystal form control agent was added, and other conditions and steps were the same as those of example 1, specifically as follows: (1) Weigh 300 parts of steel slag and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0105] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0106] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0107] (4) Take 30 parts of γ-type dicalcium silicate mineral, add 20 parts of GCA02 water-based epoxy curing agent and stir evenly to obtain component B.

[0108] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0109] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0110] (7) Leave the components in the air to dry naturally for 24 hours.

[0111] Comparative Example 3 In step (4) of comparative example 3, no dicalcium silicate mineral was added, and other conditions and steps were the same as those of example 1, as follows: (1) Weigh 300 parts of raw steel slag, 5 parts of magnesium chloride crystal form control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0112] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0113] (3) Taking 10 parts by weight of the modified steel slag powder as a coating modification component, add it into 20 parts of a diethanolamine-modified cationic waterborne epoxy resin emulsion and stir evenly to obtain component A.

[0114] (4) Take 20 parts by weight of GCA02 water-based epoxy curing agent as component B.

[0115] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0116] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0117] (7) Leave the components in the air to dry naturally for 24 hours.

[0118] Comparative Example 4 In step (4) of comparative example 4, the alkalinity control agent is ordinary Portland cement, and other conditions and steps are the same as those of example 1, specifically as follows: (1) Weigh 300 parts of raw steel slag, 5 parts of magnesium chloride crystal form control agent, and 1000 parts of water by weight, add them into a mixer and mix for 2 hours. After being fully mixed, put them into a 60℃ oven to dry for 24 hours, and then put them into a ball mill to grind for 0.5 hours.

[0119] (2) The ground powder is passed through a 200-mesh sieve to obtain the slag powder under the sieve. The powder under the sieve is spread out and placed in a CO 2 The pressure tank is controlled at 95% humidity, heated to 90°C by a thermocouple, and a high concentration of CO with a volume concentration of 99.9% is introduced. 2 The gas is heated to a pressure of 0.2 MPa and modified for 2 hours to obtain modified steel slag powder, which is then taken out for later use.

[0120] (3) Take 10 parts by weight of the modified steel slag powder as a coating modification component, add it to 20 parts of diethanolamine modified cationic waterborne epoxy resin emulsion, stir evenly and let stand for 0.5 h to obtain component A.

[0121] (4) Take 30 parts of ordinary Portland cement, add 20 parts of GCA02 water-based epoxy curing agent and mix well to obtain component B.

[0122] (5) Evenly mix the above components A and B, add 1 part of isopropyl alcohol diluent, mix thoroughly to obtain a finished coating.

[0123] (6) Remove defects and damaged parts on the concrete surface, use high-pressure water to remove surface dust and debris, and after the concrete surface is dry, use a brush roller to evenly apply the above coating on the concrete surface. Apply 2 to 3 times in total, and control the coating thickness to 1 to 1.5 mm.

[0124] (7) Leave the components in the air to dry naturally for 24 hours.

[0125] Experimental Group The above Examples 1 to 7 and Comparative Examples 1 to 4 were subjected to an impact and abrasion strength test (underwater steel ball method), with reference to the industry standard DL / T 5150-2020 "Test Procedure for Hydraulic Concrete", and a speed of 1500 r / min was selected for 72 hours of impact and abrasion.

[0126] The above Examples 1 to 7 and Comparative Examples 1 to 4 were subjected to a pull-off adhesion test, with reference to GB / T5210 "Pull-off adhesion test for paints and varnishes".

[0127] The test results are shown in Table 1.

[0128] Table 1 Performance test results of Examples 1 to 7 and Comparative Examples 1 to 4

[0129] It can be seen from Table 1 that, compared with comparative examples 1 to 7, the water-based anti-corrosion coating for abrasion-resistant hydraulic concrete prepared in Examples 1 to 4 of the present invention can effectively form a coating with higher abrasion resistance and bonding strength, which is suitable for harsh scouring environments such as oceans and high-drop rivers, and the preparation process is simple and easy to construct.

[0130] The specific implementation methods of the present application described above do not constitute a limitation on the protection scope of the present application. Any other corresponding changes and modifications made according to the technical concept of the present application should be included in the protection scope of the claims of the present application.

Claims

1. A water-based anti-corrosion coating for abrasion-resistant hydraulic concrete, characterized in that: The raw materials include, by weight: 10 to 40 parts of waterborne epoxy resin emulsion, 10 to 40 parts of modified steel slag powder, 10 to 50 parts of alkaline regulator, and 10 to 40 parts of waterborne epoxy curing agent.

2. The water-based anti-corrosion coating for hydraulic concrete resistant to abrasion according to claim 1 is characterized in that: The preparation steps of the modified steel slag powder include: The steel slag, the crystal form control agent and water are mixed uniformly, and then dried, ball-milled and sieved to obtain the undersize; The sieve material is subjected to carbonization modification treatment to obtain modified steel slag powder.

3. The water-based anti-corrosion coating for hydraulic concrete resistant to abrasion according to claim 2 is characterized in that: The crystal form control agent is at least one of magnesium chloride, magnesium sulfate, potassium chloride and sodium phosphate; and / or, The amount of the crystal form control agent added is 0.5-3% of the mass of the steel slag; and / or, The amount of water added is 1 to 10 times the mass of the slag; and / or, The mesh size of the sieve is 100 to 300 meshes; and / or, During the carbonization modification process, the humidity is 90% to 95%, the temperature is 70 to 90° C., the air pressure is 0.2 to 0.3 MPa, the carbonization time is 1 to 3 hours, and the volume concentration of CO2 gas is 40 to 100%.

4. The water-based anti-corrosion coating for hydraulic concrete resistant to abrasion according to claim 1 is characterized in that: The aqueous epoxy resin emulsion is a cationic aqueous epoxy resin emulsion; and / or, The solid content of the waterborne epoxy resin emulsion is 30-60%; and / or, The curing agent is at least one of 8310 self-emulsifying epoxy curing agent, GCA02 water-based epoxy curing agent, and 810 curing agent; and / or, The alkaline regulator is a dicalcium silicate mineral.

5. The water-based anti-corrosion coating for abrasion-resistant hydraulic concrete according to claim 4 is characterized in that: The waterborne epoxy resin emulsion is an amine-modified cationic waterborne epoxy resin emulsion; and / or, The alkaline control agent is at least one of γ-type dicalcium silicate and β-type dicalcium silicate.

6. The water-based anti-corrosion coating for hydraulic concrete resistant to abrasion according to claim 1, characterized in that: The raw materials include, by weight: 20 parts of waterborne epoxy resin emulsion, 10 to 40 parts of modified steel slag powder, 10 to 30 parts of alkaline regulator, and 20 parts of waterborne epoxy curing agent.

7. The water-based anti-corrosion coating for hydraulic concrete resistant to abrasion according to claim 1, characterized in that: The raw materials of the water-based anti-corrosion coating for anti-abrasion hydraulic concrete also include: diluent; wherein, The diluent is at least one of anhydrous ethanol, ethylene glycol, propylene glycol, and isopropanol; and / or, The added amount of the diluent accounts for 0.05-5% of the total mass of the abrasion-resistant hydraulic concrete water-based anti-corrosion coating.

8. A method for preparing the water-based anticorrosive coating for abrasion-resistant hydraulic concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: The water-based epoxy resin emulsion, modified steel slag powder, water-based epoxy curing agent and alkaline regulating agent are uniformly mixed to obtain a water-based anti-corrosion coating for abrasion-resistant hydraulic concrete.

9. A water-based anti-corrosion coating for abrasion-resistant hydraulic concrete, characterized in that: The abrasion-resistant hydraulic concrete water-based anti-corrosion coating is obtained by applying the abrasion-resistant hydraulic concrete water-based anti-corrosion coating according to any one of claims 1 to 7 to the surface of a substrate and drying the coating.

10. The water-based anti-corrosion coating for abrasion-resistant hydraulic concrete according to claim 9, characterized in that: The substrate is concrete; and / or, The thickness of the water-based anti-corrosion coating of the anti-abrasion hydraulic concrete is 0.5 to 3 mm and / or The drying method is natural drying, and the drying time is 12 to 36 hours.

Citation Information

Patent Citations

  • A wear-resistant coating made from steel slag, a wear-resistant coating block, and a preparation method thereof.

    CN107189627B

  • Wear-resistant paint prepared from steel slag, wear-resistant paint coating block and preparation method

    CN107189627A

  • Water-proof steel slag aggregate with strong adhesion to asphalt and preparation method thereof

    CN110104981A

  • Modified steel slag pigment filler, epoxy paint formed by modified steel slag pigment filler, and preparation method and application of epoxy paint

    CN112210231A

  • High-performance steel slag cold-mixed and cold-laid wearing layer material and preparation method thereof

    CN118439821A